2009
DOI: 10.1002/iub.252
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐214 is aberrantly expressed in cervical cancers and inhibits the growth of HeLa cells

Abstract: SummaryMicroRNAs are a group of endogenously expressed, singlestranded, 18-24 nt RNAs that regulate diverse cellular pathways. Although documented evidence indicates that some microRNAs can function as oncogenes or tumor-suppressors, the role of miR-214 in regulating human cervical cancer cells remains unexplored. We determined the expression level of miR-214 and found it is downregulated in cervical cancer compared with normal tissue. Overexpression of miR-214 in HeLa cells, a human cervical cancer cell line,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
103
1
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 113 publications
(113 citation statements)
references
References 33 publications
8
103
1
1
Order By: Relevance
“…Overexpression of miR-214 in HeLa cells also significantly inhibited cell proliferation. In addition, HeLa cells that stably overexpressed miR-214 downregulated the expression of MEK3 and JNK1 at both the mRNA and protein levels by targeting the 3'UTRs of these genes (22). Finally, it has been reported that miR-34a inhibits invasiveness through regulation of the Notch pathway and its downstream matrix degrading enzyme in cervical cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of miR-214 in HeLa cells also significantly inhibited cell proliferation. In addition, HeLa cells that stably overexpressed miR-214 downregulated the expression of MEK3 and JNK1 at both the mRNA and protein levels by targeting the 3'UTRs of these genes (22). Finally, it has been reported that miR-34a inhibits invasiveness through regulation of the Notch pathway and its downstream matrix degrading enzyme in cervical cancer (23).…”
Section: Discussionmentioning
confidence: 99%
“…It has been documented to be aberrantly expressed in many tumors including breast, cervical, hepablastoma, pancreatic and lung cancer (Yanaihara et al, 2006;Magrelli et al, 2009;Yang et al, 2009;Zhang et al, 2010Derfoul et al, 2011. Accumulating evidence indicated that miR-214 functions either as onco-gene or tumor suppressor gene in different tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that microRNAs (miRNAs) act as crucial modulators in cancer progression by targeting mRNAs through cleavage or transcriptional repression (Bartel, 2004). Various miRNAs have been shown to exhibit differential expression between cervical cancer and normal cervical tissues (Wang et al, 2008), and several reports have demonstrated the roles of miRNAs in the proliferation (Yang et al, 2009), apoptosis (Li et al, 2011), and prognosis (Hu et al, 2010) of cervical cancer. However, the role of miRNAs in mediating sensitivity of cells to chemotherapeutic drugs has not been explored in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%